The distribution function of power of dissipative formations in raw materials during MHT-drying - Пак, Андрій Олегович (Technology audit and production reserves, 2012)
The task of investigation of development of dissipative formations in raw materials during mixed heat transfer drying was set. The analytical appearance of distribution function of power of dissipative formations was established